On the Complementarity between Education and Training in Europe - Giorgio Brunello (Institute for the Study of Labor (IZA), 2001)
This paper is an empirical investigation of the complementarity between education and training in 13 European countries, based on the European Community Household Panel (ECHP). After confirming the standard result that training incidence is higher among individuals with more education, I find that the relationship between educational attainment and training incidence varies significantly across countries and birth cohorts. I show that individuals have a higher training incidence in countries with a more educated labor force, a less stratified schooling system, a higher union density and a lower value of the Kaitz index. I also find evidence that individuals with more education and limited labor market experience enjoy higher private returns from recent training than individuals with the same experience and less education. More experienced individuals with higher education, however, have lower returns from recent training than less educated workers with the same experience.
Keywords: J31; J24; 330; Education; training; Europe; Bildung; Bildungsverhalten; Berufsbildung; Weiterbildung; Schätzung; EU-Staaten